12. VALUE OF SURFACE ECG IN PREDICTING THE MECHANISM OF PAROXYSMAL SUPRAVENTRICULAR TACHYCARDIA WITH REGULAR NARROW QRS COMPLEX WITHOUT PREEXCITTION SYNDROME (Vietnam Journal of Community Medicine, 2024)
Introduction: Diagnosing the mechanism of Paroxysmal Supraventricular Tachycardia helps select medications to relieve and prevent attacks, choose the vascular access route, predict the results of intervention, shorten procedure time and X-rays. This research helps determine the value of surface ECG in predicting the mechanism of Paroxysmal Supraventricular Tachycardia.Objective: To determine the value of surface ECG in predicting the mechanism of paroxysmal supraventricular tachycardia with narrow QRS complex without pre-excitation syndrome. Methods: Descriptive cross-sectional design with retrospective analysis of paroxysmalsupraventricular tachycardia patients with narrow QRS complexes who were examined and electrophysiologically ablated at Thong Nhat Dong Nai General Hospital from October 2022 to September 9 2023.Results and conclusion: The average age of patients was 51.20 ± 11.24 years old, with more women than men in the paroxysmal supraventricular tachycardia group. Surface electrocardiogram standards that had predictive value for paroxysmal supraventricular tachycardia included the following standards: r’/V1; Pseudo s’ wave in/DII,DIII,aVF and notch in aVL had corresponding sensitivity, specificity, positive predictive value as: r’/V1 (80%; 100%; 100%), wave s’pseudo/DII,DIII,aVF (64%; 100%; 100%) and aVL (68%; 100%; 100%). Surface electrocardiogram criteria that had predictive value in predicting VT included clear P wave criteria; ST-T changes and QRS amplitude alternation had corresponding sensitivity, specificity, and positive predictive value of: clear P’ waves (84%; 63.6%; 87.5%), ST-T conversion (90%; 88%; 75%) and QRS LPBD (80%; 96%; 88.9%).
Keywords: Paroxysmal supraventricular tachycardia, reentrant tachycardia at the atrioventricular node, atrioventricular reentrant tachycardia, surface electrocardiogram, arrhythmia.